RESEARCH IN THE FIELD OF TECHNICAL EXPERTISE AND TRACK REHABILITATION FOR A COAL MINING MACHINE TYPE M4A T2052-78 - Liviu Marius CÎRȚÎNĂ; Constanța RĂDULESCU (Fiabilitate şi Durabilitate)
The following paper presents data obtained following a technical expertise, extensive technical inspections followed by the preparation of technical projects, technical documentation for authorization, technical details on the execution of repairs/remediation for equipment in the surface mining industry, carried out by the author together with a team of specialists in the field for the Company Complexul Energetic Oltenia S.A. Thus, between the University "Constantin Brâncuși" of Târgu Jiu and the Company Complexul Energetic Oltenia S.A. there are data contained in Contract no.2490 /CEOSE/15.11.2016, entitled: Elaboration of documentation for the "Rehabilitation and modernization of the M4A Coal Mining Machine - including the track" - Rovinari S.E..